A ANALISIS IMPLEMENTASI MODEL PROBLEM BASED LEARNING (PBL) DALAM MENGEMBANGJAN KEMAMPUAN BERPIKIR KRITIS PESERTA DIDIK - Arina Hidayati, Ayu; Hidayanti, Denok Mugi; Neviyani, Neviyani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2025)
Education plays a fundamental role in shaping individuals who are intelligent, religious, and of good character, thereby enabling them to contribute to the progress of the nation. In the context of strengthening 21st-century learning that emphasizes critical thinking skills, this study aims to examine the effectiveness of the Problem Based Learning (PBL) model in developing students' critical thinking abilities in economics subjects, specifically on the topic of payment systems and instruments. This study uses a qualitative approach with a case study design at MA Nurul Iman Sumberjambe Jember. The research subjects include economics teachers, X IPS class students, the principal, and the curriculum deputy. Data collection techniques include observation, interviews, and documentation, while data analysis is conducted through data condensation, presentation, and conclusion drawing, with validity tested through triangulation. The research results show that the application of the PBL syntax—comprising problem analysis, diagnosis, and alternative solutions—systematically fosters the critical thinking skills of students. That ability is evident in the processes of information search, logical reasoning, cause-and-effect analysis, and solution formulation for contextual economic problems. This research provides a new contribution in affirming the effectiveness of PBL in economic learning, which has not been extensively studied in depth, particularly on the topic of payment systems and instruments. Therefore, PBL has proven to be a relevant and applicable model in creating active, reflective, and meaningful economic learning.